PEMBANGUNAN PELEMBAGAAN PARTAI PERSATUAN INDONESIA (PERINDO) SEBAGAI PARTAI POLITIK BARU DI INDONESIA - Muhammad, Hatta Abdi (Jurusan Ilmu Sosial dan Ilmu Politik Fakultas Hukum Universitas Jambi, 2018)
Political parties are the most important consensus in a country that applies a democratic system. The presence of political parties is considered as the main access link between the government and the community which is also a tool to provide life expectancy to the community. But with the competition between political parties and parts in order to have further existence, the presence of political parties must have a strong and rooted institutionalization of organizations. This article explains the process of building the institutionalization of the Persatuan Indonesia Party in the context of new political parties. A finding in this study is that the institutionalization of the Persatuan Indonesia Party is still weak.